Konsep Syirik dalam Perspektif Gus Baha: Sebuah Tinjauan Melalui Penelitian Kepustakaan - Muhammad Wahyudi Hanggara; Fatihani Istighfarin; Muhammad Imamul Muttaqin (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2025)
This study explores the concept of shirk from the perspective of Gus Bahauddin Nursalim, a contemporary Islamic scholar known for his contextual and accessible approach to religious teachings. The urgency of this study lies in the growing need for a nuanced understanding of shirk in the midst of complex modern religious practices and interpretations. This article aims to examine the concept of shirk from the perspective of Gus Bahauddin Nursalim, focusing on the division of shirk jali and khafi, and to offer practical solutions for Muslims in avoiding shirk in their daily lives. Employing a qualitative library research method, this study draws upon secondary sources such as scholarly journals and audiovisual lectures to examine Gus Baha’s interpretation. It also uses secondary data obtained from previous researchers' research journals on Google Scholar and several YouTube videos. Gus Baha is one of the students of KH. Maimun Zubair, who now manages the LP3IA Islamic boarding school and is an activist in the Lajnah Mushaf Team at the Institute of Tafsir Al-Quran of the Islamic University of Indonesia, based on the results of the study, it was found that Gus Baha emphasized that arrogance, arrogance and lust in oneself are the sources of unconscious shirk. Shirk is a great sin that means uniting Allah SWT with other creatures. Gus Baha distinguishes two types of shirk: official shirk (jali) and unofficial shirk (khafi). Official shirk is carried out openly and deliberately, while unofficial shirk is carried out secretly and unconsciously. To avoid shirk, Gus Baha invited Muslims to Defeat Lust, Practice Surah Al-Fatihah, and Practice the Tawadhu Attitude.